Medicine during the Nazi period and the Holocaust: what are the implications? An interview with Volker Roelcke - Volker Roelcke; Vivian Mannheimer (História, Ciências, Saúde: Manguinhos, 2022)
Abstract In this interview, Volker Roelcke explains and analyzes historical evidence refuting erroneous assumptions about medical atrocities committed by physicians during the Nazi era, provides insight into the implications of medicine during the Nazi period and the Holocaust for medicine and bioethics today, analyzes the history of the term “genocide,” and suggests formats for future teaching, among other topics.